Determinan Kepuasan Pengguna Software Akuntansi - Agustini, Luh De Leony; Juliarsa, Gede (E-Jurnal Akuntansi, 2024)
This study examines the influence of the Quality of Accounting Information Systems, Perceived Usefulness, Perceived Ease of Use on Accounting Software User Satisfaction at PT. Sejahtera Indo Bali, with a sample of 42 people. By using multiple linear regression analysis, the findings prove that the quality of accounting information systems and perceived ease of use have a positive effect on user satisfaction of accounting software, while perceived usefulness does not have a positive effect on user satisfaction of accounting software. In addition, the Technology Acceptance Model (TAM) model is able to explain the factors that influence user satisfaction with accounting software. Keywords: Accounting Information System Quality; Perceived Usefulness; Perceived Ease Of Use